2019
DOI: 10.3390/met9050510
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Reduction and Melting Mechanism of Sinter with Different MgO Content

Abstract: Adding MgO to sinter is considered to be a popular counter measure to cope with the use of high Al2O3 ores. The purpose of this paper is to investigate the effect of the MgO content on the reduction melting behavior in order to clarify the main mechanism of melting and dripping under simulated blast furnace (BF) conditions. It was found that reduction behavior was inhibited with an increased MgO content; the reduction mechanism was further investigated by means of XRD, SEM, and kinetic analysis. The influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The Ti-bearing primary slag assigned to CaO-MgO-Al 2 O 3 -SiO 2 -TiO 2 -FeO system with high basicity and a significant amount of FeO has different viscous behaviour to the slag in hearth. Recently, the usage of low-cost and high-alumina iron ore is gradually increased because of continuous consumption of the ores rich in iron [7,8]. Al 2 O 3 content in the slag may reach a certain level [9] and the relative amount of TiO 2 changes.…”
Section: Introductionmentioning
confidence: 99%
“…The Ti-bearing primary slag assigned to CaO-MgO-Al 2 O 3 -SiO 2 -TiO 2 -FeO system with high basicity and a significant amount of FeO has different viscous behaviour to the slag in hearth. Recently, the usage of low-cost and high-alumina iron ore is gradually increased because of continuous consumption of the ores rich in iron [7,8]. Al 2 O 3 content in the slag may reach a certain level [9] and the relative amount of TiO 2 changes.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of MgO or Al 2 O 3 content on the SM properties of sinter and pellets has been reported in many studies in the literature. The works of Guo et al [19,20] demonstrated that the softening temperatures and the maximum pressure drop increased, and the melting temperature interval became wide with the increasing MgO content in sinter, because the MgO existed as a wüstite solid solution when sinter softened, and then on melting it brought a high-melting point slag. Li et al [21] conducted a study of the effect of MgO content on the SM performance of high-gangue sinter and partially supported Guo's viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Higuchi et al [24] highlighted that when the sinter had low Al 2 O 3 , high MgO, and 1.0-1.5 basicity, the T S and T D is the best. Guo et al [25] considered that the reduction behavior was inhibited by the increase in MgO content through the study on the high-temperature reduction and melting mechanism of sinters with various MgO content.…”
Section: Introductionmentioning
confidence: 99%